Independent domestication events in the blue‐cheese fungus Penicillium roqueforti. Issue 14 (3rd February 2020) - Dumas, Emilie; Feurtey, Alice; Rodríguez de la Vega, Ricardo C.; Le Prieur, Stéphanie; Snirc, Alodie; Coton, Monika; Thierry, Anne; Coton, Emmanuel; Le Piver, Mélanie; Roueyre, Daniel; Ropars, Jeanne; Branca, Antoine; et al.
Abstract: Domestication provides an excellent framework for studying adaptive divergence. Using population genomics and phenotypic assays, we reconstructed the domestication history of the blue cheese mould Penicillium roqueforti. We showed that this fungus was domesticated twice independently. The population used in Roquefort originated from an old domestication event associated with weak bottlenecks and exhibited traits beneficial for pre‐industrial cheese production (slower growth in cheese and greater spore production on bread, the traditional multiplication medium). The other cheese population originated more recently from the selection of a single clonal lineage, was associated with all types of blue cheese worldwide except Roquefort, and displayed phenotypes more suited for industrial cheese production (high lipolytic activity, efficient cheese cavity colonization ability and salt tolerance). We detected genomic regions affected by recent positive selection and putative horizontal gene transfers. This study sheds light on the processes of rapid adaptation and raises questions about genetic resource conservation. Abstract : see also the Perspective by Brigida Gallone, Jan Steensels and Kevin J. Verstrepen.